STUDI PERBANDINGAN PEMBELAJARAN YANG MENGGUNAKAN METODE SMALL GROUP DISCUSSION DENGAN METODE DRILL PADA MATA PELAJARAN MATEMATIKA KELAS III MIN PEMURUS DALAM BANJARMASIN - Hermaniah, Hermaniah (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2017)
Learning method is the way teachers plan learning activities to achieve student learning outcomes and desired learning objectives, small group discussion method and drill method are the good learning methods used in the field of mathematics. This research aims to; (1) to know how the implementation of learning using small group discussion method and drill method for the grade III mathematics in MIN Pemurus Dalam Banjarmasin, (2) to know how the learning result of the students using group discussion method and drill method on the subjects of mathematics for the grade III MIN Pemurus Dalam Banjarmasin, (3) To find out whether there is a significant difference between the learning result of the students using small group discussion method and the learning result of the students using drill method in the third grade of mathematics in MIN Pemurus Dalam Banjarmasin. Type of field research approach is presented in descriptive qualitative and quantitative. Population and research sample of students of class III A and III B MIN Pemurus Dalam Banjarmasin. Data collection techniques are test, documentation and observation. Data taken from the pretest and posttest values. The pretest and posttest instruments used are the same as the validity value of the content and reliable and the data analysis using U test. The result of the research shows that (1) The implementation of small group discussion method of learning goes well, in doing the student worksheet, each group performs its duty by cooperating with a group of friends to solve a problem related to the material described earlier. At the time of learning, drill method is also given several exercises to be solved individually by students, on the learning the teacher guides students for those who do not understand about the exercises given. (2) Result of study in the experimental class of small group discussion method for student learning increase 30 points with good qualification. While the learning outcomes in the experimental class of drill method of student learning outcomes increased 26.06 points with good qualification. (3) Based on the test result with U test, Ha test rejected and Ho accepted. So it can be concluded that there is no significant difference between student learning result using small group discussion method with drill method.